The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12913-018-2839-x
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the CR-POSSUM model in surgery for colorectal cancer in Spain (CCR-CARESS study) and comparison with other models to predict operative mortality

Abstract: Background: To validate and recalibrate the CR-POSSUM model and compared its discriminatory capacity with other European models such as POSSUM, P-POSSUM, AFC or IRCS to predict operative mortality in surgery for colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
0
16
0
1
Order By: Relevance
“…POSSUM AND P-POSSUM were original scoring systems which enumerated the mortality and morbidity in a patient undergoing major surgeries [10,11]. These have been validated in numerous studies outside the UK, and their value in surgical audit has been proven beyond doubt [12][13][14]. A study conducted by the American College of Surgeons (ACS-NSQIP) in 2005 to 2006 showed that ten procedure groups among various general surgical operations accounted for 62% of complications, and colectomy was topping in the list [15].…”
Section: Discussionmentioning
confidence: 99%
“…POSSUM AND P-POSSUM were original scoring systems which enumerated the mortality and morbidity in a patient undergoing major surgeries [10,11]. These have been validated in numerous studies outside the UK, and their value in surgical audit has been proven beyond doubt [12][13][14]. A study conducted by the American College of Surgeons (ACS-NSQIP) in 2005 to 2006 showed that ten procedure groups among various general surgical operations accounted for 62% of complications, and colectomy was topping in the list [15].…”
Section: Discussionmentioning
confidence: 99%
“…Reasons include the limited discriminatory power of some, the complexity of the calculations required, and the large number of variables that must be taken into account, some of which are not recorded routinely. A recent validation of the POSSUM, Portsmouth (P) POSSUM, colorectal (CR) POSSUM, Identification of Risk in Colorectal Surgery (IRCS) and Association Française de Chirurgie (AFC) models in a multicentre cohort in Spain concluded that none obtained optimal discriminatory power (all had area under the receiver operating characteristic (ROC) curve (AUC) values below 0·70), as also found by others. Some of the variables included in some of these models (such as urea, blood loss or surgical technique) are not available before the intervention, and this limits their utility.…”
Section: Introductionmentioning
confidence: 99%
“…Surgery is essential in many cases of CRC and is associated with considerable mortality (up to 11% at 30 days) and a high rate of complications 6,7. Many factors are associated with outcomes after different types of surgery, and COPD has been associated with increased short-term mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Surgery is essential in many cases of CRC and is associated with considerable mortality (up to 11% at 30 days) and a high rate of complications. 6 , 7 Many factors are associated with outcomes after different types of surgery, and COPD has been associated with increased short-term mortality. However, few studies of postoperative outcomes in patients with COPD focus on patients with CRC or on postoperative outcomes other than mortality, such as reintervention, complications, or length of stay (LOS).…”
Section: Introductionmentioning
confidence: 99%